Digital transformation and pandemic: New paradigms - Figueroa Gutarra, Edwin (2022)
In many ways, the COVID-19 pandemic has compromised the development of the nations, configured a number of restrictions to the fundamental rights and radically changed the lives of human beings in several negative aspects. However, there are also aspects that, as a result of the virus, are being redirected and that pose major challenges for the Judiciaries. Hence, it may be argued that these are new paradigms that allow us to rethink the judicial work and assume a relevant role in the digital transformation of the work of judges. Aspects, such as virtual hearings, the demand for investment in technology and a new approach in the role of judges to increase their use of artificial intelligence tools, imply important changes both in the present and in the years to come, and at the same time become paradigms with a view to improving the new tasks of judges.